A Systematic Literature Review: Cyber Attack: Phishing Environments, Techniques, and Detection Mechanism - Cindy Natasya; Irvin Irvin; Alexander Agung Santoso Gunawan (International Journal of Computer Science and Humanitarian AI, 2024)
In this digital era, phishing has attacked many platforms such as email, website, message, link form. Phishing is an act of creating a website that is exactly like the original website that is used to take someone's personal data. Phishing causes loss of customer confidence to use any application or website. Most of the victims of phishing are people who do not understand phishing or an organization. This kind of cyber-attacks consist of various types and countermeasures that need to be considered for the public user to prevent phishing based on phishing techniques, educate individuals about these attacks, and encourage the use of phishing prevention techniques. This paper consists of types of phishing and awareness to wary of phishing to overcome them. Therefore, the goal of this study is to identify the most typical environments for phishing attacks in order to ascertain the most popular media and technique. The authors of this study plan to conduct a Systematic Literature Review (SLR) of studies that have been done on the subject that was just described. The authors come to the overall conclusion that a website is the ideal option for phishing attacks using social engineering techniques. Additionally, the authors offer numerous suggestions for preventing phishing with various techniques. However, the most effective defense against phishing attacks is identification of phishing attempts through education and training.